2001
DOI: 10.1063/1.1331075
|View full text |Cite
|
Sign up to set email alerts
|

Nb interaction with hydrogen plasma

Abstract: Plasma driven permeation of hydrogen through Nb: influence of the surface and bulk defects AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…3 (4 · 10 23 H/m 2 ) was reached with no noticeable decrease in the absorption rate. The negligible reemission after such a significant dose at an elevated temperature (450°C) is explained by a very low value of k r0 (and a 0 ) typical for the Nb surface covered by O segregating in the form of a monolayer from the metal bulk [6,7]. Hydrogen retention in the panel was also investigated by keeping the panel at room temperature and it was found that most of the absorbed hydrogen was retained in the panel even after 48 h as indicated by open squares in Fig.…”
Section: Absorption Capability Of Nb Panelmentioning
confidence: 94%
See 2 more Smart Citations
“…3 (4 · 10 23 H/m 2 ) was reached with no noticeable decrease in the absorption rate. The negligible reemission after such a significant dose at an elevated temperature (450°C) is explained by a very low value of k r0 (and a 0 ) typical for the Nb surface covered by O segregating in the form of a monolayer from the metal bulk [6,7]. Hydrogen retention in the panel was also investigated by keeping the panel at room temperature and it was found that most of the absorbed hydrogen was retained in the panel even after 48 h as indicated by open squares in Fig.…”
Section: Absorption Capability Of Nb Panelmentioning
confidence: 94%
“…In the case of a Nb panel of 1 mm thickness at 200°C (the hydride phase does not form at T > 160°C), G H can be estimated as $10 24 H/m 2 taking d = 0.1, n H = 0.25 [7], a 0 = 10 À5 [6] and j i = 10 20 H/m 2 s. Fig. 1 shows a schematic view of the experimental device.…”
Section: Absorption Capability Of Panel Made Of Va-group Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…3͒, and therefore one can estimate the ␣ H magnitude to be in the order of at least 0.1. Atomic beam experiments with a number of metals covered by nonmetallic monolayers yielded ␣ H value in the range of 0.1-0.4 at T S ജ 298 K, 1,4,5,22,26,27 while the data on the superpermeation of H atoms through Nb covered by oxygen monolayer [1][2][3]17,18 are most self-consistent at ␣ H Ϸ 0.2-0.3. Taking that into account, we set ␣ H Ϸ 0.25 in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…[1][2][3] Besides, the measurement of C O can be a method to predict the surface reactivity in addition to the conventional methods of surface analysis such as x-ray photoelectron spectroscopy and Auger electron spectroscopy ͑AES͒ incapable to measure a small concentration of holes in a near-monolayer coverage.…”
mentioning
confidence: 99%